Jenis Sarana Dan Kualitas Bakteriologi Sumber Air Bersih Di Desa Bale Donggala Sulawesi Tengah: The Types of Facilities and Bacteriological Quality of Clean Water Sources in Bale Village, Donggala District, Central Sulawesi - Sapriana, Sapriana; Sasmita, Hanum (Media Publikasi Cendekia Indonesia, 2024)
Background: E. coli contamination of clean water has had a widespread impact, especially on human health. Aims: To determine the bacteriological content of clean water in Bale Village. Methods: This was a descriptive observational study conducted in July 2021. Primary data was obtained from E-Coli testing results at the Environmental Health Department Laboratory of the Palu Health Polytechnic using the MPN (Most Probable Number) method, and observations of clean water facilities. The population size was 386 clean water facilities, with a sample of 24 clean water samples. The sampling technique used the Simple Random Sampling method. Furthermore, the data was analyzed by comparing the laboratory test results with the 2017 Ministry of Health Regulation. Results: Only 1 water source met the requirements and no E.Coli was found, namely in Hamlet 2, while water sources in other hamlets were contaminated with E.Coli ranging from 4 - 2400 MPN/100 ml, and some even exceeded that number. Conclusion: The majority of clean water sources in Bale Village do not meet the requirements. Out of 24 clean water samples tested, only 1 sample met the requirements, namely the clean water sample from the water pump.